THE USE OF POGIL MODEL (PROCESS-ORIENTED GUIDED-INQUIRY LEARNING) TO ‎INCREASE THE CONCEPT UNDERSTANDING OF STUDENTS ON REACTION RATE ‎TOPIC - Aulia, Hanna; Saridewi, Nanda; Yunita, Luki (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This study aims to determine the effect of application of POGIL model in improving student` understanding of the material on reaction rate. The method used in this research is Quasi Experiment with Non Equivalent Control Design research descriptions and sampling with purposive sampling technique.The instrument used in this research are 12 essay test instrument with conceptual understanding indicator covering ability to comprehend, apply, and analyze. In this reseacrh, obtained pretest score of control class as much as 26,10 and experiment class 24,86. Next, the score of posttest of concrol class is 62,48 and experiment class is 76,48. Based on the hypothesis test with the level of trust Î± (0,05) obtained by t-test of posttest data obtained that the value of sig (2-tailed) 0,00 < 0,005 and tcount< ttabel (6,521<2,045) which mean H0 rejected and H1 accepted so that it can be concluded that there is a significant influence on the application of POGIL model to student understanding of the material on the rate of reaction. Keywords :Concept Understanding; POGIL; Reaction Rate Â